Causation and Laws of Nature - Kistler, Max (Routledge Studies in Contemporary Philosophy, 2007)
This is the first Eng translation of Causalite´ et Lois de La Nature, and is an important contribution to the theory of causation. Max Kistler reconstructs a unified concept of causation that is general enough to adequately deal with both elementary physical processes, and the macroscopic level of phenomena we encounter in everyday life. This book will be of great interest to philosophers of science and metaphysics, and also to students and scholars of philosophy of mind where concepts of causation and law play a prominent role.